Enzyme leakage from spermatozoa of Black Bengal and beetal bucks during freezing with various cryoprotectants - SINGH, M P; SINHA, A K; SINGH, BALRAJ; SINGH, D K (The Indian Journal of Animal Reproduction, 2023)
The present experiment was conducted to study the effect of cryoprotectants (glycerol, DMSO + IJand lactose) containing extenders on leakage of acrosin and hyaluronidase enzymes from spermatozoaof Black Bengal and Beetal bucks. Activities of acrosin and hyaluronidase were assayed in neat,equiliberated (pre-freezing) and frozen thawed (post-freeze) semen samples. The variations in acrosinactivity at pre- and post-freeze stages due to extender were significant (P
Keywords: Acrosin; Hyaluronidase; Buck; spermatozoa